Kajian Penerimaan Dan Penggunaan Virtual Private Network (VPN) Dalam Pelaksanaan Kegiatan Kasir. Studi Kasus Pada PT Duta Karimah - Mohammad Noviansyah (LPPM Universitas Bina Sarana Informatika, 2017)
VPN is a network that connects local communications media through the public network. Studies on the acceptance of the use of this system PT Duta Karimah Bekasi is one of the problems that exist at the moment because it is not known for certain level of acceptance on the checkout day to day operations . Therefore, it is necessary to study the factors that influence the acceptance of the use of the VPN system. This study adopted the UTAUT model developed by Venkates et al (2003). The data sample used as many as 103 data taken from the questionnaire. The purpose of the study to determine the factors that influence the acceptance of the use of a VPN and also look at the moderating effects of gender , education , and experience in the acceptance of the VPN system . Data processing method using Structural Equation Modeling (SEM) with AMOS 18.0 software. Research suggests a causal relationship performance expectancy (performance expectations) with User Behavior (Behavior acceptance of use) is a significant causal relationship that occurs as much as 5.8 %. The study also concluded that the effort expectancy (EE), Social Influence (SI), and facilitating conditions (FC) had no effect on user behavior.